A Study on the Conch Shell Industry in West Bengal - Paul, Anamitra; Jana, Sebak Kumar (Arthshastra Indian Journal of Economics & Research, 2014)
From time immemorial, West Bengal has been famous in the field of conch shell handicrafts. The gifted artisans produce wonderful objects of craft from conch shell materials. Their rare artistic skills have been streamlined in manufacturing exquisite household pieces. The present paper focused on identifying the present condition of the conch shell industry in the state, and the challenges faced by the artisans for continuing their handicraft work. The research paper is based on primary survey of 240 household conch shell units in four districts of West Bengal namely North 24-Parganas, Purba Medinipur, Paschim Medinipur, and Bankura. The paper tried to identify the major problems faced by the craftsmen in the industry. The survey revealed that irregularity in the supply and continuous increase in prices of raw materials and monopoly of raw material suppliers caused great frustration to many household entrepreneurs. The study also found that despite the poor conditions of artisans, the conch shell industry still plays an important role in creating artistic value for the artisans by maintaining and carrying forward the cultural and religious legacy of the conch shells and also generates livelihood through creation of employment and income for the artisans.